2006
DOI: 10.1111/j.1365-2648.2006.03838.x
|View full text |Cite
|
Sign up to set email alerts
|

Conceptions of pain among Somali women

Abstract: Nurses must strive for increased cultural competence and explore ways to make healthcare services sensitive to culturally diverse groups. Nurses have an educational role in educating parents and children about pain and the importance of sufficient pain relief. All healthcare providers should be aware of their own cultural values and the risk of stereotyping people.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 14 publications
2
38
0
2
Order By: Relevance
“…A few, contextually-based studies offer valuable insights on Somali women’s unique health needs and perspectives (Carroll et al, 2007a; Finnström & Söderhamn, 2006; Straus, McEwen, & Hussein, 2009; Uvall, Mohammed, & Dodge, 2009). Learning more about the Somali women who have settled into Minnesota will provide evidence-based ideas for culturally competent care and culturally specific programs.…”
Section: Background On Immigrant Healthmentioning
confidence: 99%
“…A few, contextually-based studies offer valuable insights on Somali women’s unique health needs and perspectives (Carroll et al, 2007a; Finnström & Söderhamn, 2006; Straus, McEwen, & Hussein, 2009; Uvall, Mohammed, & Dodge, 2009). Learning more about the Somali women who have settled into Minnesota will provide evidence-based ideas for culturally competent care and culturally specific programs.…”
Section: Background On Immigrant Healthmentioning
confidence: 99%
“…Tiilikainen traces a history of relating bodily ills to divine causation and an understanding of bodies as contiguous with their environments. The study of Somali women in Finland by Finnström and Söderhamn found that some Somali women identified pain as a purely physical experience while others interpreted pain as ‘something deeper', imbricated in emotional and bodily experiences 7. These fluctuating definitions of pain make sense considering the Somali word xanuun means both pain and illness 8.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Irritable Bowel Syndrome is reported more commonly in Western than Eastern women, possibly because of the belief that bowel function is private and can be a source of shame [7]. Somali women are expected not to complain of pain and Somali men are expected to be even more enduring than women are [8]. Similarly, Hispanic women in the USA were found to be more tolerant of pain because their family is given a higher priority over their pain [9].…”
Section: Introductionmentioning
confidence: 99%